“Modelo Médico Hegemónico”: usos y apropiaciones de una categoría antropológica entre trabajadores/as de la salud en Argentina - Paula Estrella; María Pozzio; Candela Heredia; Florencia Pelagagge; Horacio Pereyra (Revista del Museo de Antropología, 2026)
The “Hegemonic Medical Model” (HMM) category, of anthropological origin, has become popular among healthcare professionals, becoming a native category. The objective of this article is to describe and analyze the uses and appropriations of this category by those working in the healthcare field in Argentina. Using a collective ethnography situated in multiple contexts, we analyze the circulation and uses of HMMs working within the Health-Disease-Care processes in various healthcare institutions. The fieldwork records we selected and analyzed were conducted between 2018 and 2024. The results reveal the phenomenon in multiple contexts, for example, in educational settings where students use the HMM category very differently from medical professionals working in healthcare teams. As final considerations and in order to continue reflecting, we point out that the meanings, uses and appropriations presented demonstrate that the MMH constitutes a living category that fulfills diverse functions, is used by students to explain the chains that keep a discipline in a subordinate position and points out inter-professional tensions in health teams, among medical and non-medical health personnel, such as social workers, occupational therapists, nurses, and administrators, among others; therefore, it is possible to affirm that, as such, it will continue to spread.